TRADISI KLIWONAN: AKULTURASI BUDAYA ISLAM JAWA - Muhamad Taufik Hidayat (IBDA': Jurnal Kebudayaan Islam, 2012)
This article discusses the cultural assimilation of Kliwonan tradition with Islamic teachings. Author took some views of Clifford Geertz to explore the phenomenon of Kliwonan tradition. In that way, it is understood that there is a correlation between the pattern of Javanese life with the teachings of Islam as something noble. Kliwonan done congregational tradition and intimacy occurs between them. People who do become tradition Kliwonan feel close to the Creator, the Almighty God. Tradition as a medium to get closer through the inner region.